1988
DOI: 10.1093/jac/22.supplement_b.135
|View full text |Cite
|
Sign up to set email alerts
|

Spiramycin uptake by alveolar macrophages

Abstract: The in-vitro and in-vivo uptake of spiramycin by human and animal alveolar macrophages was studied. In-vitro penetration was studied in guinea pig and human alveolar macrophages incubated in medium 199 at 37 degrees C containing spiramycin at various concentrations. Results were expressed as the cellular/extracellular concentration ratio (C/E). The in-vivo study was performed in patients receiving 500 or 1000 mg spiramycin every 8 h as a 1-h infusion on day 1. A single infusion was given on day 2, 2 h before s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
17
0

Year Published

1990
1990
2015
2015

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 0 publications
0
17
0
Order By: Relevance
“…**, P < 0.01; *, P < 0.05. of antibiotics taken up and concentrated by leukocytes; as a result, they can reach intracellular concentrations far higher than those attained in the extracellular medium (8,21,28). Furthermore, their different pharmacokinetic properties, especially with respect to their biological half-lives and intracellular concentrations at a given time (9,16,27,28), could explain their differential effects on IL-6 production within the same group. Indeed, differences in their interactions with phagocytes have already been shown (24,32).…”
Section: Resultsmentioning
confidence: 99%
“…**, P < 0.01; *, P < 0.05. of antibiotics taken up and concentrated by leukocytes; as a result, they can reach intracellular concentrations far higher than those attained in the extracellular medium (8,21,28). Furthermore, their different pharmacokinetic properties, especially with respect to their biological half-lives and intracellular concentrations at a given time (9,16,27,28), could explain their differential effects on IL-6 production within the same group. Indeed, differences in their interactions with phagocytes have already been shown (24,32).…”
Section: Resultsmentioning
confidence: 99%
“…In cases of lower respiratory tract infections, chemical analysis of sputum (6,9,28) and analyses of tissue biopsy specimens and bronchoalveolar lavage fluid (15,32), epithelial lining fluid (4,35), and alveolar macrophages (12,13) have been performed to obtain information about the penetration of antibiotics into the lungs (3,16). However, the determination of concentrations of antibiotics in sputum is unreliable.…”
Section: Discussionmentioning
confidence: 99%
“…Concentrations of antibiotics have been measured in sputum samples (6,9,19,28), bronchoscopically harvested biopsy specimens, and bronchoalveolar lavage fluids (15,32). More sophisticated approaches include the determination of antibiotic concentrations in epithelial lining fluid (4,35) or in alveolar macrophages (12,13). Recently, imaging procedures such as planar gamma scintigraphy (21) and positron emission tomography (39) were applied to support the definition of optimal dosing schedules for respiratory tract infections.…”
mentioning
confidence: 99%
“…Prior to measuring antimicrobial agent concentrations in AMs, the in vitro efflux characteristics must be examined, and it must be ensured that significant efflux does not occur during the BAL procedure. This important validation step has not been taken for most studies (10,23,46). Only two of the published studies of antimicrobial agent concentrations in human AMs in vivo have addressed this problem, and these studies examined azithromycin, which has been shown to efflux from phagocytes very slowly (5,17), so that significant efflux during BAL is unlikely.…”
Section: Introductionmentioning
confidence: 99%